Factors That Influence Teacher Job Satisfaction At The Nurrahman Hakim Araha Foundation - Indri Guslina; Alvi Nurlaili Rahmah; Giharjo Giharjo (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study intends to analyze the following: 1) The Nurrahman Hakim araha Foundation's Work Environment Effect on Teacher Job Satisfaction; 2) The Nurrahman Hakim araha Foundation's Motivation Effect on Teacher Job Satisfaction; 3) The Nurrahman Hakim araha Foundation's Organizational Culture Effect on Teacher Job Satisfaction; and 4) The Nurrahman Hakim araha Foundation's Work Environment, Motivation, and Organizational Culture Together Effect on Teacher Job Satisfaction. Research of this kind is quantitative in nature. Forty teachers from the Nurrahman Hakim Araha Foundation made up the study's sample. In this study, a questionnaire was employed as the data gathering method. methods for analyzing data that make use of multiple and simple linear regression. There is a known 83.6% influence from the Work Environment Research results on Job Satisfaction. According to research findings, motivation has an 82% influence on job satisfaction. According to research findings, organizational culture has an 85% influence on job satisfaction. Meanwhile, the Nurrahman Hakim Araha Foundation's research on the effects of work environment, motivation, and organizational culture on teacher job satisfaction has found that these factors have an 88.3% influence. This study demonstrates how the Nurrahman Hakim Araha Foundation's teacher job satisfaction is impacted by the work environment, motivation, and organizational culture.